Analisis Penerapan Metode Activity Based Costing dalam Penetapan Tarif Jasa Rawat Inap di Rumah Sakit Umum Daerah Kota Mataram - Kusuma Dewi, Kartika Maharani; Suhaedi, Wirawan (Universitas Hamzanwadi, 2025)
This study aims to analyze and compare the determination of inpatient service rates at Mataram City Regional General Hospital using the Activity-Based Costing (ABC) method. The research process includes activity identification, cost classification, and cost driver determination to allocate costs more accurately. The method used is qualitative descriptive analysis, with data obtained through observation, interviews, and documentation studies. The results show that the ABC method produces more accurate rate calculations than traditional methods, because costs are allocated based on activities that actually consume resources. The implications of this study are expected to help hospitals in setting rates that are more transparent and accurate, and reflect the actual costs of healthcare services, thereby improving the efficiency of hospital financial management.